Pan-Cancer Analysis of the Prognostic and Immunotherapeutic Value of PDGFB - Bai Y; Wang X; Wang B (ImmunoTargets and Therapy)
Yuwei Bai,1,2 Xiaoyun Wang,1,2 Bei Wang1,2 1Institute of Integration of Traditional Chinese and Western Medicine, The Hospital Affiliated to Jiangnan University, Wuxi, People’s Republic of China; 2Wuxi School of Medicine, Jiangnan University, Wuxi, People’s Republic of ChinaCorrespondence: Bei Wang, Email xuewuhenwang@126.comIntroduction: Cancer is a widespread epidemic that affects millions of individuals across the world. Identifying novel cancer targets is crucial to developing more effective cancer treatments. Platelet-derived growth factor-B (PDGFB) plays a critical role in various tumor processes, including angiogenesis and lymphatic metastasis. However, there is a lack of research on the role of PDGFB in these processes.Methods: To address this issue, we conducted a comprehensive analysis utilizing multiple online databases to investigate the expression, prognostic, tumor stemness, and immunological effect of PDGFB. In addition, clinical samples were validated using immunohistochemistry.Results: Our findings revealed that PDGFB was highly expressed in a diverse range of cancer types, and its expression and genetic modifications were significantly associated with clinical outcomes in certain tumors. In general, high expression of PDGFB in tumors is associated with poor prognosis. Surprisingly, PDGFB was found to be highly expressed in renal clear cell carcinoma but was associated with good prognosis. In contrast, PDGFB was low expressed in lung carcinoma, but its expression was found to improve patient survival. These findings demonstrate the complex role of PDGFB in different cancer types. The study also demonstrated that PDGFB was linked to RNA and DNA stemness in 15 and 36 tumor types, respectively, and had a positive association with tumor lymphocyte infiltration. Notably, PDGFB was found to be associated with immune modulators. PDGFB, which is involved in various immune responses, influences the malignant characteristics of various cancer types and controls immune cell infiltration. We confirmed that PDGFB positively correlated with CD8 and PDL1 expression in lower grade glioma.Conclusion: This study concludes that PDGFB may serve as a potential prognostic marker and a potential targetable pathway in cancer immunotherapy. Overall, the study sheds new light on the role of PDGFB in cancer and highlights its potential clinical significance.Keywords: PDGFB, pan-cancer, prognosis, immune cell infiltration, biomarker